2001
DOI: 10.1046/j.1365-3040.2001.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

δ13C of CO2 respired in the dark in relation to δ13C of leaf metabolites: comparison between Nicotiana sylvestris and Helianthus annuus under drought

Abstract: 505Plant, Cell and Environment (2001) 24, 505-515 intercellular partial pressure of CO 2 ; PPFD, photosynthetic photon flux density; R, dark respiration; R VPDB , 13 C/ 12 C ratio of standard VPDB; R s , 13 C/ 12 C ratio of sample; Rubisco, ribulose 1,5 bisphosphate carboxylase-oxygenase; RWC, leaf relative water content; VPD, vapour pressure deficit; d 13 C, carbon isotopic composition. INTRODUCTIONCarbon isotope discrimination during leaf CO 2 assimilation has been extensively studied and models have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
164
2
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 21 publications
14
164
2
3
Order By: Relevance
“…Nevertheless, this observation agrees with some published studies in other species (Lawlor, 1976;Loboda, 1993;Flexas et al, 2005). However, several other authors have found different results on the effect of water stress on respiration, ranging from decrease (Brix, 1962;Brown and Thomas, 1980;Palta and Nobel, 1989;Escalona et al, 1999;Ghashghaie et al, 2001;Haupt-Herting et al, 2001) to stimulation (Upchurch et al, 1955;Shearmann et al, 1972;Zagdań ska, 1995). In all cases, as in this study, changes in respiration were much less than those in photosynthesis, causing a significant increase in the respiration/photosynthesis ratio under water stress, indicating that the role of respiration becomes more important as water stress develops.…”
Section: The Effect Of Water Stress On Leaf Respirationcontrasting
confidence: 53%
“…Nevertheless, this observation agrees with some published studies in other species (Lawlor, 1976;Loboda, 1993;Flexas et al, 2005). However, several other authors have found different results on the effect of water stress on respiration, ranging from decrease (Brix, 1962;Brown and Thomas, 1980;Palta and Nobel, 1989;Escalona et al, 1999;Ghashghaie et al, 2001;Haupt-Herting et al, 2001) to stimulation (Upchurch et al, 1955;Shearmann et al, 1972;Zagdań ska, 1995). In all cases, as in this study, changes in respiration were much less than those in photosynthesis, causing a significant increase in the respiration/photosynthesis ratio under water stress, indicating that the role of respiration becomes more important as water stress develops.…”
Section: The Effect Of Water Stress On Leaf Respirationcontrasting
confidence: 53%
“…During the night the 13 C-enriched transitory starch is used for sucrose synthesis. As a result, a ∼4 ‰ δ 13 C oscillation between light-and dark-exported sucrose has been predicted and observed (Ghashghaie et al, 2001;Tcherkez et al, 2004;Gessler et al, 2008Gessler et al, , 2009a.…”
Section: M12mentioning
confidence: 82%
“…Despite early evidence by Park and Epstein (1961), carbon isotope fractionation during dark respiration has long been considered negligible (Lin and Ehleringer, 1997). Systematic studies by Duranceau et al (1999) and Ghashghaie et al (2001) with a range of C 3 species again provided clear evidence for substantial and systematic variation in carbon isotope ratios of leaf dark respiration (see review by Ghashghaie et al, 2003). These authors introduced the term "apparent respiratory fractionation" to describe the manifested differences between carbon isotope compositions of leaf dark-respired CO 2 and its putative substrates (mainly carbohydrates), caused by multiple processes in the respiratory pathways (see below).…”
Section: Post-carboxylation and Respiratory Fractionationmentioning
confidence: 99%